Epidemiology, Health Care Resource Utilization, and Costs of Hemophilia A and B by Treatment Regimen: A Retrospective Analysis of German Claims Data from 2016 to 2021 - Obermüller, Dominik; Berger, Karin; Klamroth, Robert; Kleppisch, Maria; Rauchensteiner, Stephan; Ecke, Ines; Hermann, Sandra; Pawlowska-Phelan, Dorota; Häckl, Dennis; Kisser, Agnes (Hämostaseologie, 2025)
In Germany, hemophilia patients with a severe bleeding phenotype receive lifelong prophylactic treatment with intravenous concentrated factor VIII (FVIII) or IX (FIX) to prevent bleeding events. To assess the economic value of emerging treatment options, studies describing the economic burden of hemophilia under the current standard of care in Germany are needed.This study classified hemophilia A (HA) and B (HB) patients by treatment regimen in administrative claims data to examine the real-world economic burden of Hemophilia in Germany from 2016 to 2021.Hemophilia patients were identified in InGef statutory health insurance claims data via ICD-10 codes D66 (HA) and D67 (HB) in combination with one or more claims for hemophilia-related medication.Each patient's factor regimen was classified as either indicative of a severe phenotype needing prophylaxis or a non-severe phenotype treated on demand using a classification threshold of 100,000 International Units (IU) FVIII/year (HA) and 80,000 IU FIX/year (HB). Health care resource utilization and cost outcomes were captured for each study year.Male prevalence per 100,000 ranged from 6.39 to 7.81 (HA) and 1.26 to 1.89 (HB), with 43 to 53% (HA) and 40 to 56% (HB) categorized as severe. In 2021, mean (standard deviation [SD]) per-patient medication costs were €321,987 (€157,915) in the severe treatment group versus €43,487 (€92,821) in the non-severe group for HA and €289,411 (€132,400) versus €19,253 (€23,655) for HB.The results demonstrate the high economic burden of severe HA and HB in Germany, driven by the need for continuous factor replacement therapy, and give an estimate of treatment costs based on a real-world therapy mix.
Keywords: hemophilia A; hemophilia B; health care resource utilization; healthcare costs; Germany